Adam Bede - Eliot, George; General Editor Maine, G. F. (London Gollins, 1965)
Arthur's seduction of an innocent, young country girl results in remorse, suffering, and regret.
Include Epilouge and Bibliography
Keywords: England -- Infanticide -- Triangles (Interpersonal relations)